The Role of Edmund Muskie in American Foreign Policy towards the American Hostage Crisis in Iran (May 8, 1980-January 20, 1981) - Al-Zuhairi , Lect. Dr. Adnan Khairy Muzail (Thi Qar Arts Journal, 2022)
The research dealt with the role of Edmund Muskie in liberating the American hostages held in Iran, as Edmund Muskie assumed the position after the resignation of his predecessor Cyrus Vance due to the latter's objection to President Jimmy Carter's policy and his failure to liberate the hostages. An intense diplomatic approach and it was an important element and an effective planner in his country's policy towards that crisis, the outcome of which was the success in releasing the American hostages held in Iran, but the issue of the hostages affected the policy of neutrality declared by Washington when the Iran-Iraq war broke out and this war led Muskie to follow a policy Contradictory towards Iraq is more like a formal rapprochement and then siding with Iran in an attempt to approach it in order to release the American hostages being held by it.